Initial arterial access used and associated factors in coronary procedures: A retrospective study from a tertiary indian center - Abhijit Vilas Kulkarni; Adefres Bahiru; D. Manjunath; Mohan J. Murali; Hina Khaleel (PLoS ONE, 2026)
Background Transradial access (TRA) is increasingly preferred over transfemoral access (TFA) for coronary procedures due to its safety profile. However, uptake varies across clinical settings, particularly in complex and high-risk patients. Objective To assess arterial access site utilization (TRA vs TFA) and associated clinical and procedural factors in patients undergoing coronary procedures performed by a single operator at a tertiary center. Methods We conducted a retrospective review of 250 patients who underwent coronary procedures between September 2024 and February 2025, all performed by a single operator. Demographic, clinical, and procedural data were analyzed to evaluate factors associated with arterial access choice. Logistic regression models were used to determine predictors of access site. Results TFA was used in 52.8% and TRA in 47.2% of procedures. TRA was more common in stable patients and for diagnostic angiography (68% vs 32%), while TFA was preferred in emergencies, LV dysfunction, and complex multivessel disease. Independent predictors of TFA included older age (OR 1.021; p = 0.049), mild/moderate LV dysfunction (ORs 2.93 and 3.16, respectively), and prior CABG (p = 0.01). TRA was associated with fewer complications and was never used in unstable patients. Access site choice was also significantly associated with coronary disease burden and treated vessel complexity. Conclusion Despite global trends favoring TRA, TFA remains predominant in high-risk and complex cases in our setting. Tailoring access strategies based on patient risk and procedural complexity remains essential.